2018
DOI: 10.1177/1557085118773434
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Women’s Prison Sentences: Exploring the Nexus Between Motherhood, Drug Offense, and Sentence Length

Abstract: Drawing upon focal concerns and familial paternalism frameworks, we explore the effects of motherhood, various maternal indicators, and type of offense on prison sentences using official and self-report data on 419 incarcerated women in the United States. Results revealed that drug offenders were sentenced more leniently than other offenders, whereas mothers were not sentenced differently from women without children. Mothers who lived with their children received shorter prison terms than mothers who were abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…Consistent with much of the research on female prisoners (Giallombardo, 1966; Kolb & Palys, 2018), the staff with whom we spoke stated that incarcerated women placed a high value on forming close relationships with other incarcerated women. Many women in prison were mothers (Cho & Tasca, 2019); notably, we were told that the greatest pain of imprisonment was the separation from family and that this was the most frequent complaint voiced by incarcerated women. Staff recognized that many women formed tightknit friendships or pseudofamilies with other women to cope with or make up for these losses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with much of the research on female prisoners (Giallombardo, 1966; Kolb & Palys, 2018), the staff with whom we spoke stated that incarcerated women placed a high value on forming close relationships with other incarcerated women. Many women in prison were mothers (Cho & Tasca, 2019); notably, we were told that the greatest pain of imprisonment was the separation from family and that this was the most frequent complaint voiced by incarcerated women. Staff recognized that many women formed tightknit friendships or pseudofamilies with other women to cope with or make up for these losses.…”
Section: Resultsmentioning
confidence: 99%
“…Incarcerated women differ significantly from their male counterparts in terms of prior histories and pathways to crime (Belknap, 2014; Bloom et al, 2004; Daly, 1992). They are more likely to have experienced physical or sexual abuse, have substance abuse problems, or to be incarcerated for non-violent offenses (see, e.g., Chesney-Lind, 1997; Cho & Tasca, 2019; DeHart et al, 2013). Because female offenders face gender-specific adversities, they require treatment strategies that are specifically designed to address their needs (Covington & Bloom, 2006; Pollack, 2005; Wattanaporn & Holtfreter, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although majority of these studies revealed racial and ethnic differences in sentencing outcomes for female drug offenses, Cho and Tasca (2019) found no racial or ethnic differences in sentence length for female drug offenses in Arizona. Consistent with previous sentencing research (see Brennan & Spohn, 2009), these findings seemed to suggest that legal factors matter more than extralegal factors for sentence length among females.…”
Section: Females Chivalry and Sentencing Researchmentioning
confidence: 93%
“…These perceptions that guide judges to make sentencing decisions can reflect their stereotypes of certain individuals and communities. This is captured by their patterned responses to some types of criminal cases (Cho & Tasca, 2018;Spohn & Cederblom, 1991;Steffensmeier & Demuth, 2001). For example, focusing on court decisions in communities that are more politically conservative, Helms and Jacobs (2002) find offenders who are unemployed, male, and black are perceived to pose a higher threat to the local communities; hence, offenders with these characteristics received longer sentences in court.…”
Section: The Contextual Nature Of Parole Practicementioning
confidence: 99%